Analisis Kepuasan Mahasiswa Prodi Manajemen Pendidikan Islam terhadap Pelayanan Akademik Fakultas Tarbiyah dan Keguruan UIN Sulthan Thaha Saifuddin Jambi - Lallo Lallo; Lukman Hakim; Dian Nisa Istofa (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2020)
This study aims to analyze the satisfaction of MPI students to the academic services of FTK UIN Sulthan Thaha Saifuddin Jambi. Research using quantitative approach method with non experiment type survey method. Variables used include independent variables, namely student satisfaction levels, and dependent variables that are academic services. Data is collected through observations, documentation, and questionnaires. The results of the study found the results of calculations with product moment correlation techniques obtained rhitung 0.673 greater when compared to apostates at a significant level of 5% = 0.138 and a significant level of 1% = 0.181. So the Zero Hypothesis is rejected, meaning there is student satisfaction with academic services. While the alternative hypothesis is accepted, there is no student satisfaction with the academic services of the faculty of tarbiyah and teaching.